Road Traffic Accidents in Kathmandu Valley - Shrestha, Bikash Kumar (The Third Pole: Journal of Geography Education, 2014)
This paper describes the situation of road traffic accident in Kathmandu valley for the last five years. It has focused on the causes, vehicle-types commonly involved and the trends of deaths. Based on secondary data, this study has also come up with some discussions on the preventive solution. As Road Traffic Accidents (RTAs) has been proved one of the major challenging issues of Kathmandu Valley, the concerned authority should come up with a decisive role in mitigating deaths and causalities due to this phenomenon. DOI: http://dx.doi.org/10.3126/ttp.v13i0.11547 The Third Pole Vol. 13, 2013 Page: 54-56